Pharmacy stock inventory system - Siti Fairuz, Mohd Razali (2005)
A pharmacy stock inventory system (PSIS) is a computerized system designed for user to manage the stock of the drugs inventory and monitoring the stock facility. The stand alone pharmacy stock inventory system provides alert of expire drugs and minimum quantity of each drugs and also searching algorithm technique applied in this system. A research and analysis on the current system and searching technique was done to get better understanding of the system. The RAD methodology was used in this project development implements iterative development which is suitable for stand alone applications requirements that changes from time to time. Testing is done every phase of the development life cycle to make sure that the system working properly. This project was developed using Visual Basic 6.0 and Microsoft Access 2000 as a database platform. As a final result,this system was fulfilled all the research objectives.This research was successfully developed the PSIS prototype system, computerized and optimized the current system using String Search Algorithm.